(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Coronary artery disease (CAD) remains a leading global health burden, driven by a combination of modifiable and non-modifiable risk factors. This study evaluates key risk factors, including dyslipidemia, hypertension, diabetes mellitus, smoking, obesity, physical inactivity, and emerging contributors such as chronic inflammation and elevated lipoprotein(a). Non-modifiable factors like age, gender, and genetic predisposition are also discussed. Preventive strategies involving lifestyle changes, pharmacological interventions, and advancements in precision medicine are highlighted. Effective CAD prevention and treatment requires a multi-pronged strategy that targets these risk factors; doing so has the ability to lower death and morbidity rates.